The Ordinary Envy of Aguabuena People: Revisiting Universalistic Ideas from Local Entanglements (2015)
Envy encompasses various forms of relatedness among Aguabuena people, a small potter community of rural Andean Colombia. Drawing from ethnographic material, this article explores how envy is reciprocated in three concrete scenarios (kinship, legal sues, and hydraulics), arguing for an understanding centered in envy's ordinariness and daily practices as an analytical context from where to revisit more universalistic ideas.